Peningkatan Keterampilan Kerja Pemuda melalui Pelatihan SDM berbasis Kompetensi di Yayasan Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Widowati, Widowati; Astutik, Endang Puji; Karlina, Dira (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The increasing demand for skilled labor in the workforce highlights the urgent need to equip youth with relevant competencies. In response, a community service program titled